PERANAN ORANG TUA DALAM MENGATASI SIFAT PEMALU PADA ANAK (Studi Kasus pada Anak di PAUD Terpadu Pontianak Barat) - Trijayanti, Shindy (Jurnal Edukasi Pendidikan Anak Usia Dini, 2016)
This research is motivated by the problems that exist in PAUD Terpadu Pontianak Barat is the existence of two shy child aged 5-6 years. Shyness considered reasonable behavior by some parents. The purpose of this study is to identify and describe the characteristics of a shy child, the role of parents in dealing with children who are shy and enabling and inhibiting factors in overcoming the child's parents are shy. This study used descriptive qualitative case study approach, the research conducted intensive, in-depth and trying to get information that is as complete as possible about the role of parents in overcoming a shy child. Source of data collected from the event, activity or behavior as a source of data related to the research objectives. Data collection techniques used were observation, interviews and documentation. Data collection tool that is in use that observation guide children and parents, interview parents as well as the collection of documents. Results of research conducted by the researchers, the characteristics of the child who is the subject of research meet the characters timid child that the child lacked the courage to speak, prefer to play alone, a child less open, not daring to look when invited to speak, inability to answer questions, the role of parents which can be said to be good enough to see the percentage reaches 70%, supporting factors and barriers that come from the outside and inside of a shy child.Keywords: Parents, Shyness, Children